DESIGN PRACTICE AS A CULTURAL RESPONSE TO TEXTILE WASTE AND SUSTAINABILITY VALUES - Nabilatul Fikroh; Dandi Yunidar; Lira Anindita Utami (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
Textile waste generated by the fashion industry represents not only an environmental challenge but also a cultural outcome of contemporary production systems and consumption values. In Indonesia, the dominance of synthetic materials and fast fashion practices has intensified the accumulation of textile waste, reflecting a linear perception of material use and disposal. This study explores synthetic fleece textile waste through a design-led approach, positioning design practice as a cultural and reflective response to sustainability issues rather than a purely technical solution. Using qualitative methods including field observation, interviews, visual documentation, and design-driven material exploration, the research examines fleece waste sourced from garment production in Bandung. Material exploration combines fleece fibers with potato starch as a natural binder, guided by Material Driven Design and Cradle-to-Cradle principles. Rather than emphasizing technical optimization, the study focuses on how material behavior, surface expression, and limitations inform design decisions and sustainability narratives. The findings show that fleece waste can be reframed as a meaningful material within non-structural interior applications when approached through design practice. The resulting wall clock serves as a reflective artifact that communicates material origin, transformation processes, and sustainability values within a familiar domestic context. This research contributes to design and sustainability discourse by demonstrating how design practice can transform textile waste into culturally relevant material narratives, fostering material awareness and alternative value systems in everyday life.